Assessment of influence of anti-icing fluids based on ethylene and propylene glycol on environment and airport infrastructure. (24th January 2022) - Yakovlieva, Anna; Boichenko, Sergii; Shkilniuk, Iryna; Bakhtyn, Anatolii; Kale, Utku; Nagy, András
Snow, frost, and ice on the surface of aircraft negatively affect the aerodynamic and operational properties of aircraft. Ethylene glycol and propylene glycol are the most commonly used components of anti-icing fluids for aircraft, which have a significant impact on the environment. The paper presents complex analytical review of a large number of domestic and foreign technical and regulatory information, which made it possible to carry out a comprehensive comparison of physical-chemical and operational properties of propylene and ethylene glycol-containing materials, to investigate their influence on components of ecosystems, including the human body. Comparative analysis of studies shows that propylene glycol is inert for living organisms and people. Ethylene glycol negatively affects reproductive function, metabolism, immune system and leads to a decrease in haemoglobin concentration. LD50 value for ethylene glycol is more than 4 times lower than for propylene glycol. Propylene glycol fluid is more environmentally friendly due to low toxicity, increased biological decomposition under the same operating requirements. Basing on the systematised data the general strategy for minimising the negative effects of anti-icing and deicing fluids on the environment is considered and proposed.